Mechanism for Biological Degradation of H2S Odour Gas from Livestock Farm - Liang, Mei-Sheng; Liang, Ying (Asian Journal of Chemistry, 2015)
In this paper, biological removal of H2S derived from livestock farm was investigated using a self-made biofilter with efficient bioceramics and polyhedral hollow balls. After analyzing the relationship between the mass of the microorganism degrading H2S and the total mass of input H2S, it was concluded that, in the process of degradation of H2S, the concentration of SO42- increased with time and sulfate radical could stick to the biofilter firmly. The pH value in the biofilter dropped with degradation of H2S reaction, the difference between the theoretical value of degradation of S and actual value of degradation of S was increasingly large along with the increase of inlet H2S concentration. Sulfate ion was the main product in the degradation process. Meanwhile, some of S2- and traces of S element was measured in the biological degradation of H2S process. Thus, the mechanism of microorganism degrading H2S could be obtained and it was found that the transformation of H2S (g) to H2S (l) was a key step in the biodegradation process.